Ethical and Conventional Stock Price Performance: An Empirical Investigation under CAPM-GARCH Models - Erraitab, Elmostafa; Khamlichi, Abdelbari El (International Journal of Social and Administrative Sciences, 2022)
The present paper aims to examine the financial performance of the Moroccan Ethical, Social and Governance index (ESG10) compared to its conventional counterpart the Moroccan All Shares Index MASI index. The ethical investment is a kind of investment that applies screenings criteria to include or exclude assets from a portfolio. This asset filtering strategy, however, may have additional financial costs compared with traditional investments. Therefore, we will examine the following issue: Does ethical investment impact positively/negatively on corporates’ stock market performances? The study covers the period 2019-2022. To this end, various performance ratios was used and a CAPM-GARCH model was estimated. Our findings indicate that the ethical index is not only more volatile than the conventional peer, but also shows a smaller return. This paper is one of the first studies to tackle comparative performances for the ESG 10 index, which was launched by the Casablanca Stock Exchange in September 2018.